Evaluation of Left Ventricular Diastolic Function by Echocardiography - Lacalzada, Juan; Duque, Amelia; Rosa, Alejandro de la; Barragan, Antonio; Izquierdo, María Manuela; Arroyo, Eduardo; Laynez, Ana; Laynez, Ignacio (IntechOpen, 2011)
None